سمات الأنا الشعرية الأنثوية الحداثية بين روضة الحاج وفروغ فرخزاد (مقدمة نقدية نفسية مقارنة) - Baraa Khaled Hilal (التراث الأدبي)
The poetic ego is a modern expression must distinguish the poet who has a unique poetic personality. In the modern era, Ego witnessed many transformations, with the emergence of the romantic school, but the symbolic and existential schools  created another form of the Ego, emerged from psychiatric clinics and was crystallized by the Austrian psychologist (Sigmund Freud), I intend to address one type of these new poetic transformations,   classical characteristics of Female Ego in the works of the Sudanese poet Rawdha Al-Hajj compared to the Iranian poet Forough Farrokhzad." the Sudanese I will study the classical poetic female ego and its features, in their Arabic or translated into Arabic poetry. My study will be a critical comparative study in the light of the psychological approach. The expected outcomes of the study includes but not limited to, continuation of the traditional form of the poetic ego in modern poetry, and emergence of new forms of the poetic ego weak female ego.